2018
DOI: 10.1039/c7cp08308d
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine-based small-molecule organic solar cells with power conversion efficiency over 7% and open circuit voltage of about 1.0 V using solvent vapor annealing

Abstract: We have used two unsymmetrical small molecules, named phenothiazine 1 and 2 with a D-A-D-π-D configuration, where phenothiazine is used as a central unit, triphenylamine is used as a terminal unit and TCBD and cyclohexa-2,5-diene-1,4-diylidene-expanded TCBD are used as an acceptor between the phenothiazine and triphenylamine units, as a small molecule donor along with PCBM as an acceptor for solution processed bulk heterojunction solar cells. The variation of acceptors in the phenothiazine derivatives makes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The wide scope of this “click” reaction has been recently covered in comprehensive reviews , . The push‐pull properties stemming from these donor‐substituted TCBD moieties have recently found successful applications in photovoltaic devices , . Indeed, optimal charge‐transfer is a critical parameter for the design of sensitizers for solar energy applications.…”
Section: Introductionmentioning
confidence: 99%
“…The wide scope of this “click” reaction has been recently covered in comprehensive reviews , . The push‐pull properties stemming from these donor‐substituted TCBD moieties have recently found successful applications in photovoltaic devices , . Indeed, optimal charge‐transfer is a critical parameter for the design of sensitizers for solar energy applications.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Sharma and coworkers prepared two unsymmetrical small molecules 31 and 32 with a D-A-D-p-D architecture, where the central PTZ unit is connected to terminal triphenylamine via electron-withdrawing 1,1,4,4-tetracyanobutadiene and cyclohexa-2,5-diene-1,4-diylidene moieties. 51 The optimized OSCs with 32 as the active layer exhibited a high PCE of 7.35%, while the devices with 31 showed a low PCE of 4.81%. Revoju et al further examined the effect of varying the side chain and p-conjugation length on three A-A-D-A-A type PTZ-based small molecules.…”
Section: Organic Solar Cells (Oscs)mentioning
confidence: 92%
“…Different derivatives of PTZ were also studied for the photocatalytic HER by combining them with a TiO 2 photocatalyst [13] . In addition, PTZ‐based molecules were successfully explored as hole‐transfer agents to improve the efficiency of solar cells [14] . Two main factors directly control the use of PTZ as an ideal hole‐transfer agent during the photocatalytic process: (i) one‐electron oxidation of PTZ to form the cationic radical (PTZ .+ ) with high stability and (ii) thermodynamically favorable hole transfer from the VB of g ‐CN [1.47 V vs. normal hydrogen electrode (NHE)] to the highest occupied molecular orbital (HOMO) of PTZ (0.9 V vs. NHE) [15] …”
Section: Figurementioning
confidence: 99%
“…[13] In addition, PTZ-based molecules were successfully explored as hole-transfer agents to improve the efficiency of solar cells. [14] Two main factors directly control the use of PTZ as an ideal hole-transfer agent during the photocatalytic process: (i) one-electron oxidation of PTZ to form the cationic radical (PTZ * + ) with high stability and (ii) thermodynamically favorable hole transfer from the VB of g-CN [1.47 V vs. normal hydrogen electrode (NHE)] to the highest occupied molecular orbital (HOMO) of PTZ (0.9 V vs. NHE). [15] Although Durrant and co-workers reported that the photophysics of g-CN materials are similar to that of inorganic semiconductors, [16] the role of the hole-transport agents (HTAs) on the photocatalytic properties of g-CN or, in a broader context, to photoactive organic polymers remains unexplored.…”
mentioning
confidence: 99%